PENGARUH PRILAKU KEPEMIMPINAN TUTOR BK DAN IKLIM BELAJAR TERHADAP PENGEMBANGAN KARAKTER PESERTA DIDIK DI SKB LIMBOTO GORONTALO - Abdul Rahmat (Psympathic : Jurnal Ilmiah Psikologi, 2013)
This study aimed to study the effect of behavioral counseling teacher leadership and school climate on student character development in the SKB Limboto Gorontalo. The results showed that that there is a significant positive correlation between leadership behaviors and character development. In addition, there is a significant positive correlation between school climate and character development. Leadership behavior and school climate also significantly correlate with with character development. Leadership behavior and school climate contribute to character development.